Implementation of The Covid-19 Assistance Program by Utilizing Integrated Data on Social Welfare in Medan - Nur, Siti Hazzah; Ginting, Wiro Oktavius; Afifah, Nur (Research Horizon, 2024)
Integrated Social Welfare Data (Data Kesejahteraan Sosial Terpadu/DTKS) is the main data used by the government to determine the social assistance beneficiaries. However, in terms of the use of DTKS in implementing the Covid-19 assistance program, it is still not optimal. This is because the data on poor people who are targeted by social assistance programs are invalid. There are still beneficiary aids that are not on target, resulting in duplicate data. Besides that, the problem of 4 aspects of utilization, namely knowing, understanding, owning, and utilizing, is still only 1 OPD that did all of those things. Based on this, through Regulation of the Minister of Social Affairs (Peraturan Menteri Sosial/Permensos) No. 3 of 2021 concerning Integrated Social Welfare Data Management, the Ministry of Social Affairs has built, managed, and utilized DTKS. The purpose of this research is to see how the process of using DTKS by the Office of Social Affairs in implementing social assistance programs uses qualitative research methods with a descriptive approach. Using data collection techniques from interviews, observation, and documentation studies. The results of this study indicate that the utilization of DTKS has not been maximized. This can be seen from the determination of the community that does not comply with the technical guidelines, and the targets and realization are not balanced.